ALTERNATIVE INTERCEPTIVE TREATMENT METHODS OF CLASS III MALOCCLUSION - Bogdan Dragomir; Mihnea Iacob; Cristian Romanec; Irina Zetu; Clara-Diana Haddad (Romanian Dental Association for Education, 2022)
Class III malocclusion characteristics are present and can be observed at an early age, usually between 3 and 5 years old. Orthopaedic treatment for class III skeletal problems is aimed at reducing or re-directing mandibular growth and/or enhancing maxillary growth. If left untreated, this maxillomandibular discrepancy will worsen and the majority of these patients will ultimately require orthognathic surgery as adults.Therefore, interceptive treatment is desired and should be undertaken as soon as the abnormality is diagnosed to prevent it from becoming permanent. Recently, new strategies for treating Class III malocclusions have appeared and the purpose of this systematic review and meta-analysis is to present alternative methods in the interceptive treatment of Class III malocclusion such as bone anchorage devices. Searches were made in the Pubmed, ResearchGate, SagePub, and NCBI databases, as well as in a grey literature database, and were complemented by hand-searching. However, it is reveald that skeletal anchorage appears to reduce the dentoalveolar effects while maximising the orthopaedic effect in growing patients.